Knowiedgement and attitudes of a population sample in Lima about AIDS - Pamo Reyna, Oscar (1992)
A prospective and transversal survey was carried out in work centers of Lima City between august and october 1991 in order to determine knowledgement, attitudes and predictive factors of desinformation of adult people about AIDS.A 14 items-questionnaire was taken to 942 adults literate workers. The characteristics of our sample were: between 18 and 30 years old, 52,5%; male, 66,6%; high scholarity, 88,1%; with partner, 55,5%; employees, 46,6%. We found that 89,3% had adequate knowledgment and poor level of it correlated with low scholarity, older age and to have a partner. We conclude that AIDS prevention campaigns have been effective among adult literate workers and more emphasis on subgroups with low scholarity, older and with a partner is needed.